Las condiciones sociales que limitan a los jóvenes en su participación ciudadana en el centro poblado rural de conache, distrito de laredo, en el año 2013 - Suárez Razuri, Luz Anghela (2013)
The intention of my thesis is to analyze how the social conditions of the young population, between the ages from 18 to 24 years, limit his alternatives of civil participation in Conache's Populated Rural Center in the year 2013. The descriptive methodology and it was inside the stages of compilation of information had a duration of 65 working days and inside the processing and analysis of information was of a duration of 33 working days; it constituted stages essentially ethnographic or descriptively and simultaneously, ethnological or analytical. It is demonstrated in this investigation on the social conditions of Conache's Populated Rural Center, characterized by the crisis of values and the negative attitude of the official institutions they propitiate limited modals of civil participation in the young population between the ages from 18 to 24 years.